Effects of decreases of animal pollinators on human nutrition and global health: a modelling analysis - Smith, Matthew R; Singh, Gitanjali M; Mozaffarian, Dariush; Myers, Samuel S (The Lancet (British edition), 2015)
Anthropogenic declines of animal pollinators and the associated effects on human nutrition are of growing concern. We quantified the nutritional and health outcomes associated with decreased intake of pollinator-dependent foods for populations around the world. We assembled a database of supplies of 224 types of food in 156 countries. We quantified nutrient composition and pollinator dependence of foods to estimate the size of possible reductions in micronutrient and food intakes for different national populations, while keeping calorie intake constant with replacement by staple foods. We estimated pollinator-decline-dependent changes in micronutrient-deficient populations using population-weighted estimated average requirements and the cutpoint method. We estimated disease burdens of non-communicable, communicable, and malnutrition-related diseases with the Global Burden of Disease 2010 comparative risk assessment framework. Assuming complete removal of pollinators, 71 million (95% uncertainty interval 41–262) people in low-income countries could become newly deficient in vitamin A, and an additional 2·2 billion (1·2–2·5) already consuming below the average requirement would have further declines in vitamin A supplies. Corresponding estimates for folate were 173 million (134–225) and 1·23 billion (1·12–1·33). A 100% decline in pollinator services could reduce global fruit supplies by 22·9% (19·5–26·1), vegetables by 16·3% (15·1–17·7), and nuts and seeds by 22·1% (17·7–26·4), with significant heterogeneity by country. In sum, these dietary changes could increase global deaths yearly from non-communicable and malnutrition-related diseases by 1·42 million (1·38–1·48) and disability-adjusted life-years (DALYs) by 27·0 million (25·8–29·1), an increase of 2·7% for deaths and 1·1% for DALYs. A 50% loss of pollination services would be associated with 700 000 additional annual deaths and 13·2 million DALYs. Declines in animal pollinators could cause significant global health burdens from both non-communicable diseases and micronutrient deficiencies. Winslow Foundation, Bill & Melinda Gates Foundation.